2009
DOI: 10.1179/174328809x405883
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of shoulder subluxation and its association with other post-stroke complications

Abstract: Objectives: Shoulder subluxation affects up to 81% of patients with stroke and has been the subject of clinical research studies for decades. Despite this, its role in upper limb recovery is poorly understood. Subluxation has been linked to other post-stroke complications such as pain, restricted range of motion, poor motor recovery and reflex sympathetic dystrophy. The aim of the present study is to synthesise research findings on the association between subluxation and other post-stroke complications. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 79 publications
0
18
0
2
Order By: Relevance
“…Silveira et al [15] encontraram dados semelhantes. Neste estudo, 86 % dos pacientes tiveram apenas um episódio de AVE. Outros trabalhos também evidenciaram esta prevalência [9,17,26].…”
Section: Discussionunclassified
“…Silveira et al [15] encontraram dados semelhantes. Neste estudo, 86 % dos pacientes tiveram apenas um episódio de AVE. Outros trabalhos também evidenciaram esta prevalência [9,17,26].…”
Section: Discussionunclassified
“…After a SS, the shoulder joint capsule, the surrounding tendons and the brachial plexus nerves could be pulled by the HUE [4,5] . Then, the degree of SS and upper limb dysfunction could be further aggravated [1,3] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that GHS itself may trigger additional post-stroke complications which, in turn, delay restoration of upper limb function [8][9][10]. The most notable of these are pain, altered shoulder range of motion and poor function in the affected upper limb [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%